English Vowel - Balqis Qonita; Qorri Fadhilah; Yani Lubis (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2023)
In this case the differences that exist in two different languages Pronunciation can be a barrier to communication. A speaker can cause misunderstandings when he mispronounces a word in a foreign language. English has a number and types of sounds that are very different from the number of sounds in that language. Indonesian.Also, a letter with a different word can represent a different sound. The aim of this course is to equip students with knowledge of English vowels so that they can improve the pronunciation of English words to make them better and correct. This training is conducted online via Zoom Media because You are taking the semester through the use of two approaches namely teaching and training.Although not 100% of partners succeed in producing the correct pronunciation, improvements can be seen in the pronunciation of the accompaniment. Partners, meanwhile, had a positive attitude toward the activity through active participation in the training provided and also satisfaction. From the survey data provided by the service team, partners were identified as part of the campaign.Barriers encountered during the activity were due to the partner's lack of confidence and the influence of the partner's mother tongue.